2020
DOI: 10.1042/bst20200210
|View full text |Cite
|
Sign up to set email alerts
|

Review on material parameters to enhance bone cell function in vitro and in vivo

Abstract: Bone plays critical roles in support, protection, movement, and metabolism. Although bone has an innate capacity for regeneration, this capacity is limited, and many bone injuries and diseases require intervention. Biomaterials are a critical component of many treatments to restore bone function and include non-resorbable implants to augment bone and resorbable materials to guide regeneration. Biomaterials can vary considerably in their biocompatibility and bioactivity, which are functions of specific material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…This indicated that PDLSC-based construct is promising as a tissue engineering scaffold for bone regeneration, especially the repair of craniofacial bone. However, bone is a dynamic organ, which interacts with the immune system and vascular system, future research needs to focus not only on osteogenic effect, but also on immune reaction and vascular (Madsen et al, 2020). Additionally, future in vivo study design would center on the performance of PDLSC-based constructs in various pathophysiological environments in order to achieve optimal effects.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that PDLSC-based construct is promising as a tissue engineering scaffold for bone regeneration, especially the repair of craniofacial bone. However, bone is a dynamic organ, which interacts with the immune system and vascular system, future research needs to focus not only on osteogenic effect, but also on immune reaction and vascular (Madsen et al, 2020). Additionally, future in vivo study design would center on the performance of PDLSC-based constructs in various pathophysiological environments in order to achieve optimal effects.…”
Section: Discussionmentioning
confidence: 99%
“…The cell fate could be precisely controlled by the size and shape of the 2D and 3D structures fabricated using various technologies. Both the choice of material and its design specifications have a significant impact on cell functions (Madsen et al, 2020). Most researchers manufacture substrate topographies with predetermined dimensions to stress the cells.…”
Section: Ex Vivo Design Of Synthetic Niches For Mscs Niche Sizementioning
confidence: 99%
“…The choice of material and its design features (Madsen et al, 2020), 2D and 3D tissue-like matrix (Thomas et al, 2018), and numerous complex physical (e.g., surface electric charge and free energy, temperature, fluid transport, etc. ), (bio) mechanical (e.g., stiffness, shear stress, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In order to solve the evolutionary problem defined by equation ( 6), a finite difference scheme is used, considering the linear approximation: (7) Then: (8) and the iterative algorithm is established as: (9) The algorithm defined by Eq. ( 9) is applied to the MSCs and chondrocytes as well as the TNF-α and BMP-2 concentrations.…”
Section: Diffusion Problem Numerical Approachmentioning
confidence: 99%
“…At the cell scale, obtaining data related with the bone healing process is achieved by means of investigation in vivo and in vitro [7]. Such data are very difficult to obtain due to the time involved, the expensive resources required, and the difficulty in generalizing the results.…”
Section: Introductionmentioning
confidence: 99%